PEMBUATAN KERIPIK JANTUNG PISANG KEPOK (KAJIAN PENGARUH KONSENTRASI DAN LAMA PERENDAMAN MENGGUNAKAN AIR KAPUR) - Lasar, Thomas Baha; Mushollaeni, Wahyu; Sasongko, Pramono (BUANA SAINS, 2025)
This study aims to determine the optimal concentration and soaking duration of banana flowers in lime water to produce high quality chips, as well as to analyze the financial feasibility of the production process. The study uses a Completely Randomized Design with two factors: the concentration of lime water (P) and the soaking time of banana flowers in lime water (L). The result showed that the best quality banana flower chips were obtained by soaking for 30 minutes in a 5% lime water concentration. The chips had a moisture content of 14.96%, crude fiber content of 2.49%, and ash content of 5.75% and in the preference test, with scores for taste (4.9), texture (4.7), color (4.75), and smell (4.5).